Physiological and biochemical indicator monitoring of excellent biathlon athletes during plateau training - Zhang, S. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: This article analyzes the plateau training regulation and the adapted ability of athletes through the observing and measuring variable physiological and biochemical indicators, such as serum creatine kinase (CK), hemoglobin (HB), blood urea (BUN), serum testosterone (T), blood lactic acid (BLA), ECG, blood pressure and pulse.